PENGELOLAAN UTANG DALAM PERPEKTIF ISLAM; STUDI KASUS PENGELOLAAN UTANG PADA MAHASISWA UNIMED JURUSAN KIMIA - Jahara Widyaloka; Mutiah Khaira; M. Andra Febrian Siregar; Anggita Rahma Siregar; Nova Fajria Marbun; Syifa Namira Damanik; Hapni Laila Siregar (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Debts are a common practice in daily life and are often considered trivial, especially if the amount is small. In fact, in Islamic teachings, debt is a mandate that must be fulfilled and has a moral responsibility for every individual. This research aims to find out students' views on debt practices that are considered trivial from an Islamic perspective. This study uses a quantitative descriptive approach with a survey method. The data was obtained through a questionnaire distributed online to students of the Chemistry Education Study Program, Faculty of Mathematics and Natural Sciences, State University of Medan. The data obtained is then collected and analyzed descriptively. The results of the study show that there are still views that consider small debts as not very important, even though in Islam every debt must still be accounted for.